GENE POOL FOR BREEDING MONOGERM TABLE BEET - V. I. Burenin; T. M. Piskunova; D. V. Sokolova (Труды по прикладной ботанике, генетике и селекции)
Results of studying the collection accessions of table beet with different levels of monogermity are presented. Inheritance of this character in the progeny and also its connection with other traits and properties are shown. Accessions with stable expression of monogermity and the possibility of using them in breeding are described. Promising source material for development of heterosis hybrids is recommended.